2022
DOI: 10.48550/arxiv.2203.14576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bulk-interface correspondence from quantum distance in flat band systems

Abstract: The key notion of topological analysis is the bulk-boundary correspondence, which provides us with direct access to the topological structure of a Bloch wave function via the existence of boundary or interface modes. While only the topology of the wave function has been considered relevant to boundary modes, we first demonstrate that another geometric quantity, the so-called quantum distance, can host a new kind of bulk-interface correspondence. We consider a generic class of two-dimensional flat band systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…When the Coulomb interaction between electrons is introduced, the flat bands host unconventional superconductivity [4][5][6][7][8][9][10][11][12], ferromagnetism [13][14][15][16][17][18][19], Wigner crystal [20][21][22][23], and fractional Chern insulator [3,[24][25][26][27][28][29][30][31][32][33]. The quantum distance, one of the geometric quantities of the Bloch wavefunction, plays an important role in the anomalous Landau levels [34,35], a new kind of bulk-interface correspondence [36], and appearance of the topological non-contractible loop states in flat band systems [37]. Moreover, it was revealed that the quantum metric [38] is the key quantity in the physics of the superfluidity [39,40] and orbital magnetic susceptibility [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…When the Coulomb interaction between electrons is introduced, the flat bands host unconventional superconductivity [4][5][6][7][8][9][10][11][12], ferromagnetism [13][14][15][16][17][18][19], Wigner crystal [20][21][22][23], and fractional Chern insulator [3,[24][25][26][27][28][29][30][31][32][33]. The quantum distance, one of the geometric quantities of the Bloch wavefunction, plays an important role in the anomalous Landau levels [34,35], a new kind of bulk-interface correspondence [36], and appearance of the topological non-contractible loop states in flat band systems [37]. Moreover, it was revealed that the quantum metric [38] is the key quantity in the physics of the superfluidity [39,40] and orbital magnetic susceptibility [41,42].…”
Section: Introductionmentioning
confidence: 99%